Hepatitis C in Chronic Kidney Disease After the DAA Revolution: Clinical Decisions, Transplantation, and Implementation Challenges - Mostafa Mohrag; Ali Someili; Erwa Elmakki; Mohammed Abdulrasak (Journal of Clinical Medicine, 2026)
Direct-acting antiviral (DAA) therapy has dramatically transformed the management of hepatitis C virus (HCV) infection in chronic kidney disease (CKD). Severe renal impairment and dialysis dependence are no longer considered major barriers to virologic cure. The main difficulties have shifted toward efficient diagnosis, choosing the regimen in the presence of cirrhosis and drug interactions, coordinating treatment with kidney transplantation, managing HCV-associated immune-complex kidney disease, and providing treatment in dialysis and resource-limited settings. This narrative review aims to discuss these issues in a decision-oriented manner, using verified guidelines, systematic reviews, important clinical trials, transplant cohorts, and studies of cryoglobulinemic disease, while explicitly comparing the strength and consistency of the underlying evidence and highlighting areas of genuine clinical uncertainty. Present evidence supports using the recommended DAA regimens without renal dose adjustment, while ribavirin needs dose modification when kidney function is reduced and can result in hemolytic anemia. Kidneys from HCV-viremic donors can be transplanted to recipients without HCV infection when proper informed consent, rapid access to DAA treatment, and organized post-transplant monitoring are available, although the minimum effective duration of peri-transplant antiviral prophylaxis remains unresolved. Antiviral therapy is the first-line treatment for HCV-associated glomerular disease, while rituximab-based immunosuppression is largely reserved for severe, rapidly progressive, or persistent cryoglobulinemic vasculitis. Future progress will depend less on proving antiviral efficacy and more on closing the gaps between screening, confirmatory testing, starting treatment, transplantation pathways, and long-term follow-up, gaps that stem from inequities in diagnostic infrastructure, drug reimbursement, and healthcare-system organization as much as from any remaining biomedical uncertainty.